TO ENSURE THE STABLE OPERATION OF CONTINUOUS WELDED RAIL - Zhadan, H. H. (Science and Transport Progress, 2006)
The information from history of jointless way onDonetskrailway is shown in the paper. It is considered modern condition and particularities is haved a temperature-strenuous work egalitarian stairwell of jointless way with provision for seasonal change the temperature of rails and installed periodicity of the reconstruction normative delaytion of plugging and mortage bolts.